“Embarazo en adolescentes que fueron atendidas por parto en el Hospital Obstétrico Angela Loayza de Ollague, durante el periodo de Junio a Diciembre 2014” - Vásquez Peña, Susana Briceida (2015)
Teenage pregnancy has become a health problem of first order today. Teenage pregnancy is increasingly common in our society, especially in underdeveloped and developing countries because of its social and health adverse impact for both the mother and the child.